A critical review of "travelling fire" scenarios for performance-based structural engineering. (July 2017) - Dai, Xu; Welch, Stephen; Usmani, Asif
Abstract: Many studies of the thermal and structural behaviour for large compartments in fire carried out over the past two decades show that fires in such compartments have a great deal of non-uniformity (e.g. Stern-Gottfried et al.[1] ), unlike the homogeneous compartment temperature assumption in the current fire safety engineering practice. Furthermore, some large compartment fires may burn locally and tend to move across entire floor plates over a period of time. This kind of fire scenario is beginning to be idealized as travelling fires in the context of performance-based structural and fire safety engineering. This paper presents a literature review of the travelling fire research topic and its state of the art, including both the experimental and theoretical work for the past twenty years. It is found that the main obstacle of developing the travelling fire knowledge is the lack of understanding of the physical mechanisms behind this kind of fire scenario, which requires more reasonable large scale travelling fire experiments to be set up and carried out. The demonstration of the development of a new travelling fire framework is also presented in this paper, to show how current available experimental data hinder the analytical model development, and the urgent need that the new travelling fire experiments should be conducted.